Decision-Making by Handball Referees: Design of an ad hoc Observation Instrument and Polar Coordinate Analysis - Morillo, Juan P.; Reigal, Rafael E.; Hernández-Mendo, Antonio; Montaña, Alejandro; Morales-Sánchez, Verónica (Frontiers in Psychology, 2017)
Referees are essential for sports such as handball. However, there are few tools available to analyze the activity of handball referees. The aim of this study was to design an instrument for observing the behavior of referees in handball competitions and to analyze the resulting data by polar coordinate analysis. The instrument contained 6 criteria and 18 categories and can be used to monitor and describe the actions of handball referees according to their role/position on the playing court. For the data quality control analysis, we calculated Pearson’s (<0.99), Spearman’s (<.99) and Tau Kendall’s (<0.98) correlation coefficients and Cohen’s kappa (<0.78) and Phi (<0.82) coefficients. In the generalizability analysis, the absolute and relative generalizability coefficients were 0.99 in both cases. Polar coordinate analysis of referee decisions showed that correct calls more common for central court and 7-meter throw calls. Likewise, calls were more likely to be incorrect (in terms of both errors of omission and commission) when taken from the goal-line position.